Identification of post-generation effect of 3,4-methylenedioxymethamphetamine on the mouse brain by large-scale gene expression analysis - Eun, Jung Woo; Kwack, Seung Jun; Noh, Ji Heon; Jung, Kwang Hwa; Kim, Jeong Kyu; Bae, Hyun Jin; Xie, Hongjian; Ryu, Jae Chun; Ahn, Young Min; Park, Won Sang; Lee, Jung Young; Rhee, Gyu Seek; et al. (ELSEVIER IRELAND LTD, 2010)
The compound 3,4-methylenedioxymethamphetamine (MDMA or ecstasy) is a synthetic, psychoactive drug chemically similar to the stimulant methamphetamine and the hallucinogen mescaline. Accumulated data has revealed potential toxic effects associated with MDMA on brain serotonin and dopamine neurons in animal models. However, the relevance of these adverse effects on prenatal exposure to this drug remains unknown. In this study, we demonstrated that prenatal (F0) exposure to MDMA caused permanent large-scale transcriptional changes in the brains of the offspring (F1), especially in the cerebral cortex, by gene expression profiling analysis. The expression analysis of the brain of F1 pups, after maternal ingestion of MDMA (20 mg/kg MDMA), revealed significant transcriptional changes in both male and female pups. Supervised analysis resulted in the identification of 804 outlier genes in males and 1784 outlier genes in females as MDMA-associated genes in the F1 generation. Most of the functional categories of genes, among the outlier genes, were intracellular signaling pathways, including the MAPK signaling pathway. Wnt signaling pathway, and neuroactive ligand-receptor interaction pathway. Although these genes were affected by MDMA exposure in utero, their association with brain dysfunction requires further investigation. The results of this study suggest that prenatal MDMA exposure may affect the developing brain. (C) 2010 Elsevier Ireland Ltd. All rights reserved.
Keywords: WNT SIGNALING PATHWAY; AXON TERMINALS; TRANSCRIPTIONAL RESPONSES; GENDER DIFFERENCES; SEX-DIFFERENCES; MDMA ECSTASY; NEUROTOXICITY; FOREBRAIN; DOPAMINE; RAT